Long-run profits in times of crisis: A comparison between European SMEs and large companies - Alcalde Fradejas, Nuria; Ramírez Alesón, Marisa (Estudios de Economía, 2015)
This is pioneering research in that it makes a comparison of the process of convergence of long-run profits in the manufacturing sector of six European countries (2000-12), differentiating between SMEs and large firms, and by identifying the impact of the crisis on this process. The results obtained by employing the convergence model, known as the Partial Adjustment Model, indicate that the inter-country competitive process, is working better among large companies than among SMEs. The impact of the crisis on this process has been uneven across the countries and the sizes of the firms.